Reexamining The First Hijrah as A Foundation for Ethical Pluralism in Ethiopia - Imam, Mohammad Fuyudun Ni'am; Imam Ghazali Said; Ahmad Nabilul Maram; Achmad Zainulloh Hamid (MUSLIM HERITAGE, 2025)
Abstract This article revisits the First Hijrah to Abyssinia and the Muslim community’s engagement with the Christian kingdom of Najāshī as a foundational narrative for ethical pluralism and shared political sovereignty within Islamic thought. In contrast to conventional historiography that marginalizes Islam’s role in Ethiopia’s state formation, this study foregrounds the early interfaith alliance between Muslim migrants and their Christian host, King Najāshī. Drawing on classical sources such as Ibn Hishām, al-Sarakhsī, and al-Shāfiʿī, the article reconstructs the legal and ethical discourse surrounding Muslim military involvement in Najāshī’s defense. It critiques traditional jurisprudential interpretations that condition Muslim solidarity on Najāshī’s conversion to Islam and instead emphasizes a paradigm of mutual protection founded on trust and civic responsibility. By contextualizing this episode within Ethiopia’s religious historiography and political tensions, the study challenges nationalist and colonial narratives that erase Muslim agency. The findings advocate for reviving this legacy of interfaith coexistence as a model for ethical citizenship in plural societies—affirming the right to live together through a shared commitment to justice rather than doctrinal uniformity.   Abstrak Artikel ini meninjau kembali peristiwa Hijrah Pertama ke Habasyah dan keterlibatan komunitas Muslim dengan kerajaan Kristen Najāshī sebagai narasi dasar bagi pluralisme etis dan kedaulatan politik bersama dalam tradisi pemikiran Islam. Berbeda dengan historiografi konvensional yang meminggirkan peran Islam dalam pembentukan negara di Ethiopia, kajian ini menyoroti aliansi antaragama pada masa awal antara para migran Muslim dan tuan rumah Kristen mereka, Raja Najāshī. Dengan merujuk pada sumber-sumber klasik seperti Ibn Hishām, al-Sarakhsī, dan al-Shāfiʿī, artikel ini merekonstruksi wacana hukum dan etika mengenai keterlibatan militer Muslim dalam membela Najāshī. Tulisan ini mengkritisi pandangan fikih tradisional yang menggantungkan legitimasi solidaritas Muslim pada konversi Najāshī ke dalam Islam, dan justru menekankan paradigma perlindungan timbal balik yang didasarkan pada rasa saling percaya dan tanggung jawab sipil. Dengan membingkai episode ini dalam lanskap historiografi keagamaan dan ketegangan politik di Ethiopia, studi ini menantang representasi nasionalis dan kolonial yang menghapus agensi Muslim. Temuan artikel ini menegaskan pentingnya menghidupkan kembali warisan koeksistensi lintas iman tersebut sebagai model kewargaan etis dalam masyarakat plural, yang menegaskan hak untuk hidup berdampingan melalui komitmen bersama terhadap keadilan, bukan melalui keseragaman doktrinal. Keywords: Abyssinia; Ethical pluralism; Ethiopia; Interfaith relations; Islamic political ethics